Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

Fifty years of riverine harmful algal bloom modeling: A global synthesis of approaches, challenges, and opportunities - Jennifer C. Murphy; Rebecca M. Gorney; Lisa V. Lucas; Jacob A. Zwart; Jennfier L. Graham (Water Research, 2026)

Characterizing Cooperative Extension Educators’ Practice-Based Adaptation Strategies for Nutrition Education Programs - Alexandra MacMillan Uribe; Jacob Szeszulski; Meredith Graham; Emma Lewis; Chad Rethorst; Elizabeth Racine; Roger Figueroa; Marco Palma; Amy Yaroch; Margarita Teran-Garcia; Courtney Dodd; Rebecca Seguin-Fowler (Journal of Nutrition Education and Behavior, 2026)

Gibbsite solubility and aluminum speciation in alkaline nuclear waste containing nitrate, nitrite, and phosphate - Trent R. Graham; Ashley R. Kennedy; Winnie Liu; Daria V. Boglaienko; Robert G. Felsted; Jacob G. Morton; Micah P. Prange; Mark E. Bowden; Teresa L. Lemmon; Marie S. Swita; Hsiu-Wen Wang; Michael D. Britton; et al. (Chemical Engineering Journal, 2026)

Quantitative Mineral Resource Assessment of Lithium Pegmatite Deposits in the Southern Appalachian Orogen - Joshua M. Rosera; Kelsey E. Crocker; Laura S. Pianowski; Jacob T. Murchek; Ashton M. Wiens; Margaret M. Sanders; Lucas L. Evart; Jacob DeAngelo; Graham W. Lederer; Joshua A. Coyan (Natural Resources Research, 2026)
The first quantitative mineral resource assessment for undiscovered lithium pegmatite deposits in the southern Appalachian region of the United States was conducted. Permissive tracts for lithium pegmatite deposits were delineated by integrating lithological, tectonic, geochemical, geophysical and mineral occurrence data. Lithium pegmatite prospectivity of the tracts was ranked with simplified mappable criteria, including proximity to Paleozoic felsic intrusions and major lithotectonic structures, stream sediment geochemical anomalies, and pegmatite occurrence data. The geospatial data and permissive tracts were used to estimate the number of undiscovered lithium pegmatite deposits. These estimates were integrated into probabilistic simulations along with a new global lithium pegmatite grade and tonnage dataset to quantify potential contained undiscovered lithium resources. An economic filter was applied to convert the probabilistic estimates of contained lithium into recoverable material. The identified lithium pegmatite resources for the Carolina Lithium and Kings Mountain deposits, North Carolina, contain 1589 thousand tons (kt) of Li 2 O. The median contained undiscovered resource for the southern Appalachian orogen was estimated to be 2240 kt Li 2 O. At 90% confidence, the region contains at least 130 kt Li 2 O, and 10,700 kt at 10% confidence. After applying economic filters, the median recoverable contained resource was 1430 kt Li 2 O, corresponding to approximately 201 years of current lithium imports for consumption in the United States. North and South Carolina are likely to contain most of these resources. Coarse data resolution and intra-state variations in the geological data contribute to uncertainty of undiscovered lithium pegmatite resources. Continued efforts to harmonize disparate geospatial datasets with updated or new information can improve the accuracy and precision of estimated undiscovered lithium pegmatite resources in the study area and at broader scales.

Winter bioenergetics in freshwater fishes: Knowledge gaps and model evaluation - Connor Reeve; Zoe A. Zrini; Christian J. Bihun; Lauren E. Rowsey; Megan K. Murphy; Ben Speers-Roesch; Jacob W. Brownscombe; Steven J. Cooke; Graham D. Raby (Fisheries Research, 2026)

Academic achievements after childhood meningitis: a nationwide, population-based cohort study - Emma E. Graham; Malte M. Tetens; Jacob Bodilsen; Nanna S. Andersen; Ram Dessau; Svend Ellermann-Eriksen; Kristina Franck; Sofie Midgley; Jens Kjølseth Møller; Alex Christian Nielsen; Lene Nielsen; Kirstine K. Søgaard; et al. (Infectious Diseases, 2026)

Mechanisms of Strong Hearts, Healthy Communities-2.0 Effects on Weight: A Mediation Analysis - Chad D. Rethorst; Margaret Demment; Meredith L. Graham; Seungyeon Ha; Alexandra L. MacMillan Uribe; Brian K. Lo; Jacob Szeszulski; Phrashiah Githinji; David Strogatz; Sara C. Folta; Miriam E. Nelson; Rebecca A. Seguin-Fowler (Journal of Nutrition Education and Behavior, 2026)

Hooking injury, physiological stress, and post-release activity patterns of giant trevally (Caranx ignobilis) captured using spinning gear in a catch-and-release recreational fishery - Andy J. Danylchuk; Luc LaRochelle; Graham D. Raby; Brian Bennett; Steven J. Cooke; Jacob W. Brownscombe (Environmental Biology of Fishes, 2026)

Craniofacial photography for detection of positional obstructive sleep apnoea - Kate Sutherland; John Wheatley; Kristina Kairaitis; Brendon J. Yee; Gary Cohen; Kerri Melehan; Stephen Lambert; Philip de Chazal; Peter A. Cistulli; Peter Cistulli; Philip de Chazal; Nina Sarkissian; et al. (Sleep and Biological Rhythms, 2026)
Supine-dependent OSA is a well-recognised OSA phenotype and may relate to craniofacial structure. Our aim was to assess whether craniofacial photos are able to identify positional OSA, specifically supine-isolated OSA, in comparison to non-positional OSA. Frontal and profile craniofacial photographs of participants were acquired according to a standardised protocol. Photographs were analysed and compared between non-positional and supine-isolated OSA groups. A total of 156 OSA patients were included (54.5% supine-isolated OSA, 45.5% with non-positional OSA). The supine-isolated group had a longer upper face height and greater upper-to-lower face height ratio, smaller face width, reduced face width-to-height ratio, and smaller mandibular width, length, and size of the mandibular base. Differences in facial measurements were no longer significant after adjustment for body size and OSA severity. Our study demonstrates that supine-isolated OSA can be identified using facial photography. Larger studies in groups matched for BMI and OSA severity are needed to confirm whether this technique may also capture other features related to supine-isolated OSA (i.e., differences in underlying skeletal structure).

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Decay and solid-liquid partitioning of mpox and vaccinia virus DNA in primary influent and settled solids to guide wastewater-based epidemiology practices - Jacob R. Phaneuf; Gyuhyon Cha; Janet K. Hatt; Konstantinos T. Konstantinidis; Katherine E. Graham (Water Research, 2025)

Future climate projections in the global coastal ocean - Jason Holt; Anna Katavouta; Joanne Hopkins; Laurent O. Amoudry; Christian M. Appendini; Lars Arneborg; Alex Arnold; Yuri Artioli; Jerome Aucan; Barbara Berx; Laura Cagigal; Michela De Dominicis; et al. (Progress in Oceanography, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Risk of psychiatric neurodevelopmental disorders after meningitis in childhood: a nationwide, population-based cohort study - Emma E. Graham; Malte M. Tetens; Jacob Bodilsen; Ram Dessau; Svend Ellermann-Eriksen; Nanna S. Andersen; Charlotte Sværke Jørgensen; Michael Pedersen; Kirstine K. Søgaard; Jette Bangsborg; Alex Christian Nielsen; Jens Kjølseth Møller; et al. (Infectious Diseases, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Lamb meat colour is minimally affected under reduced oxygen concentration in modified atmosphere packaging - Maddison T. Corlett; David W. Pethick; Khama R. Kelman; Robin H. Jacob; Liselotte Pannier; Ihab Habib; Graham E. Gardner (Food Packaging and Shelf Life, 2024)

Microwave pyrolysis of various wastes and analysis of energy recovery - Scarlett Allende; Graham Brodie; Mohan V. Jacob (Bioresource Technology Reports, 2024)

ELSSIE: A compact stereo spectral imager for planetary surface morphology and composition - Scott L. Murchie; Frank P. Seelos; Bethany L. Ehlmann; John D. Boldt; Lawrence E. Brown; Jacob M. Greenberg; Karl A. Hibbitts; W. Jeffrey Lees; David M. Linko; Joseph J. Linden; Graham P. Murphy; Jorge I. Núñez; et al. (Planetary and Space Science, 2024)

The CathCam: A Novel Angioscopic Solution for Endovascular Interventions - Mohammadmahdi Tahmasebi; Yara Alawneh; Jacob Miller; Alykhan Sewani; Ahmed Kayssi; Andrew Dueck; Graham Wright; Xijia Gu; M. Ali Tavallaei (Annals of Biomedical Engineering, 2023)

First report of sound production in rock bass (Ambloplites rupestris) - Jacob C. Bowman; Graham D. Raby (Environmental Biology of Fishes, 2023)

Carbon dynamics in old-growth forests of the Central Hardwoods Region, USA - Jacob S. Fraser; Lauren S. Pile Knapp; Brad Graham; Michael A. Jenkins; John Kabrick; Michael Saunders; Martin Spetich; Steve Shifley (Forest Ecology and Management, 2023)

Breakdown of biomass for energy applications using microwave pyrolysis: A technological review - Scarlett Allende; Graham Brodie; Mohan V. Jacob (Environmental Research, 2023)

Quantification of Mechanical Characteristics of Conventional Steerable Ablation Catheters for Treatment of Atrial Fibrillation Using a Heart Phantom - Jacob Miller; Alykhan Sewani; Jeffrey Rezazada; Yara Alawneh; Pedram Kazemian; Maria Terricabras; Graham Wright; M. Ali Tavallaei (Cardiovascular Engineering and Technology, 2023)

On the relevance of animal behavior to the management and conservation of fishes and fisheries - Steven J. Cooke; Heather L. Auld; Kim Birnie-Gauvin; Chris K. Elvidge; Morgan L. Piczak; William M. Twardek; Graham D. Raby; Jacob W. Brownscombe; Jonathan D. Midwood; Robert J. Lennox; Christine Madliger; Alexander D. M. Wilson; et al. (Environmental Biology of Fishes, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

An energetics–performance framework for wild fishes - Jacob W. Brownscombe; Graham D. Raby; Karen J. Murchie; Andy J. Danylchuk; Steven J. Cooke (Journal of Fish Biology, 2022)
There is growing evidence that bioenergetics can explain relationships between environmental conditions and fish behaviour, distribution and fitness. Fish energetic needs increase predictably with water temperature, but metabolic performance ( i.e ., aerobic scope) exhibits varied relationships, and there is debate about its role in shaping fish ecology. Here we present an energetics–performance framework, which posits that ecological context determines whether energy expenditure or metabolic performance influence fish behaviour and fitness. From this framework, we present testable predictions about how temperature‐driven variability in energetic demands and metabolic performance interact with ecological conditions to influence fish behaviour, distribution and fitness. Specifically, factors such as prey availability and the spatial distributions of prey and predators may alter fish temperature selection relative to metabolic and energetic optima. Furthermore, metabolic flexibility is a key determinant of how fish will respond to changing conditions, such as those predicted with climate change. With few exceptions, these predictions have rarely been tested in the wild due partly to difficulties in remotely measuring aspects of fish energetics. However, with recent advances in technology and measurement techniques, we now have a better capacity to measure bioenergetics parameters in the wild. Testing these predictions will provide a more mechanistic understanding of how ecological factors affect fish fitness and population dynamics, advancing our knowledge of how species and ecosystems will respond to rapidly changing environments.

Fish telemetry in African inland waters and its use in management: a review - Matthew J. Burnett; Gordon C. O’Brien; Francois J. Jacobs; Graham Jewitt; Colleen T. Downs (Reviews in Fish Biology and Fisheries, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Conducting and interpreting fish telemetry studies: considerations for researchers and resource managers - Jacob W. Brownscombe; Elodie J. I. Lédée; Graham D. Raby; Daniel P. Struthers; Lee F. G. Gutowsky; Vivian M. Nguyen; Nathan Young; Michael J. W. Stokesbury; Christopher M. Holbrook; Travis O. Brenden; Christopher S. Vandergoot; Karen J. Murchie; et al. (Reviews in Fish Biology and Fisheries, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Functioning of Coastal River-Dominated Ecosystems and Implications for Oil Spill Response: From Observations to Mechanisms and Models - Adam Greer; Alan Shiller; Eileen Hofmann; Jerry Wiggert; Sally Warner; Sabrina Parra; Chudong Pan; Jeffrey Book; DongJoo Joung; Steven Dykstra; Jeffrey Krause; Brian Dzwonkowski; et al. (Oceanography, 2018)

Mass coral bleaching causes biotic homogenization of reef fish assemblages - Laura E. Richardson; Nicholas A. J. Graham; Morgan S. Pratchett; Jacob G. Eurich; Andrew S. Hoey (Global Change Biology, 2018)
Global climate change is altering community composition across many ecosystems due to nonrandom species turnover, typically characterized by the loss of specialist species and increasing similarity of biological communities across spatial scales. As anthropogenic disturbances continue to alter species composition globally, there is a growing need to identify how species responses influence the establishment of distinct assemblages, such that management actions may be appropriately assigned. Here, we use trait‐based analyses to compare temporal changes in five complementary indices of reef fish assemblage structure among six taxonomically distinct coral reef habitats exposed to a system‐wide thermal stress event. Our results revealed increased taxonomic and functional similarity of previously distinct reef fish assemblages following mass coral bleaching, with changes characterized by subtle, but significant, shifts toward predominance of small‐bodied, algal‐farming habitat generalists. Furthermore, while the taxonomic or functional richness of fish assemblages did not change across all habitats, an increase in functional originality indicated an overall loss of functional redundancy. We also found that prebleaching coral composition better predicted changes in fish assemblage structure than the magnitude of coral loss. These results emphasize how measures of alpha diversity can mask important changes in the structure and functioning of ecosystems as assemblages reorganize. Our findings also highlight the role of coral species composition in structuring communities and influencing the diversity of responses of reef fishes to disturbance. As new coral species configurations emerge, their desirability will hinge upon the composition of associated species and their capacity to maintain key ecological processes in spite of ongoing disturbances.

The future trajectory of adverse outcome pathways: a commentary - Fiona Sewell; Nichola Gellatly; Maria Beaumont; Natalie Burden; Richard Currie; Lolke de Haan; Thomas H. Hutchinson; Miriam Jacobs; Catherine Mahony; Ian Malcomber; Jyotigna Mehta; Graham Whale; et al. (Archives of Toxicology, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Integrating legacy soil phosphorus into sustainable nutrient management strategies for future food, bioenergy and water security - Helen Rowe; Paul J. A. Withers; Peter Baas; Neng Iong Chan; Donnacha Doody; Jeff Holiman; Brent Jacobs; Haigang Li; Graham K. MacDonald; Richard McDowell; Andrew N. Sharpley; Jianbo Shen; et al. (Nutrient Cycling in Agroecosystems, 2016)

Field-scale study of the influence of differing remediation strategies on trace metal geochemistry in metal mine tailings from the Irish Midlands - William T. Perkins; Graham Bird; Suzanne R. Jacobs; Cora Devoy (Environmental Science and Pollution Research, 2016)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Replication and fine mapping of asthma-associated loci in individuals of African ancestry - David B. Kantor; Cameron D. Palmer; Taylor R. Young; Yan Meng; Zofia K. Gajdos; Helen Lyon; Alkes L. Price; Samuela Pollack; Stephanie J. London; Laura R. Loehr; Lewis J. Smith; Rajesh Kumar; et al. (Human Genetics, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

A comparison of storm-based and annual-based indices of hydrologic variability: a case study in Fort Benning, Georgia - Shirish Bhat; Jennifer M. Jacobs; Kirk Hatfield; Wendy D. Graham (Environmental Monitoring and Assessment, 2010)

Gold nanoparticles decorated with oligo(ethylene glycol) thiols: kinetics of colloid aggregation driven by depletion forces - Fajun Zhang; Donald G. Dressen; Maximilian W. A. Skoda; Robert M. J. Jacobs; Stefan Zorn; Richard A. Martin; Christopher M. Martin; Graham F. Clark; Frank Schreiber (European Biophysics Journal, 2008)

A comprehensive model inter-comparison study investigating the water budget during the BALTEX-PIDCAP period - D. Jacob; B. J. J. M. Van den Hurk; U. Andr; G. Elgered; C. Fortelius; L. P. Graham; S. D. Jackson; U. Karstens; Chr. Kpken; R. Lindau; R. Podzun; B. Rockel; et al. (Meteorology and Atmospheric Physics, 2001)